Testing the Impact of Education and Economic Growth on Poverty in Aceh Province: Evidence from Panel Data - Masrizal; T. Zulham; Aliasuddin; Taufiq C. Dawood (Universitas Serambi Mekkah, 2024)
Poverty is an important social problem and an interesting issue for researchers. This research examines the influence of education and economic growth on poverty in Aceh Province. Research data uses 23 districts/cities from 2011 to 2020. Data analysis uses the Random Effect (RE) method. The research results found that education had a significant negative effect. Increasing education by one year can reduce poverty by 2.72 percent. Different things were regionally found, where the influence of education only occurred in four regions, while two regions (west and south) had no effect. However, economic growth had no effect on poverty except north zone. Therefore, policymakers need to pay attention to education as an important indicator in reducing poverty and improving the quality of economic growth so that poor people can feel the benefits.